Return Migration and Entrepreneurial Success: An Empirical Analysis for Egypt - Sami Bensassi; Liza Jabbour (Global Labor Organization (GLO), 2017)
This paper explores the effect of return migration on the performance of Egyptian household firms. A growing body of evidence suggests that return migrants are more likely to become and remain entrepreneurs (Marchetta, 2012; Wahba and Zenou, 2012). The length of the miration spell, the experience and the capital accumulated overseas may influence the ability of return migrants to establish and successfully manage their firms. We expand this literature by examining the impact of return migrants on the revenue of the business units they manage. We control for several layers of selection bias, from the migration decision to the pursuit of entrepreneurial activities. Our findings suggest that two determinants of firms' revenues favour return migrants: larger starting capital and the experience accumulated abroad. These results suggest that economic policies directed at attracting return migrants should consider expanding support schemes formerly limited to the most educated migrants or to some sectors of activity as the positive impact of return migration on entrepreneurial revenues is widespread.
Keywords: F22; 330; Return Migration; Household firms